2013
DOI: 10.3892/etm.2013.1056
|View full text |Cite
|
Sign up to set email alerts
|

Expression and characterization of cecropinXJ, a bioactive antimicrobial peptide from Bombyx mori (Bombycidae, Lepidoptera) in Escherichia coli

Abstract: Insect antimicrobial peptides (AMPs) have a broad antimicrobial spectrum. To aid the characterization of the gene function and further applications, we cloned the gene of cecropinXJ into the prokaryotic expression vector pET32a and expressed cecropinXJ in Escherichia coli BL2l (DE3). Following induction by isopropyl-β-D-thiogalactoside (IPTG), a 25 kDa fusion peptide of cecropinXJ with a tagged thioredoxin (Trx) protein was highly expressed in E. coli. The yield was 10 mg/l culture medium following purificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 43 publications
1
37
1
Order By: Relevance
“…Some small α-helical peptides from insect hemolymph have antibacterial and antifungal activity. These include some cecropins (Boulanger et al, 2002; Cavallarin et al, 1998; Delucca et al, 1997; Ekengren and Hultmark, 1999; Kim et al, 2010; Vizioli et al, 2000; Xia et al, 2013) and moricins (Brown et al, 2008; Dia et al, 2008; Hemmi et al, 2002). Proline-rich peptides with antifungal activity include lebocins (Chowdhury et al, 1995; Rao et al, 2012) and metchnikowin (Levashina et al, 1995; Rahnamaeian et al, 2009; Rahnamaeian and Vilcinskas, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Some small α-helical peptides from insect hemolymph have antibacterial and antifungal activity. These include some cecropins (Boulanger et al, 2002; Cavallarin et al, 1998; Delucca et al, 1997; Ekengren and Hultmark, 1999; Kim et al, 2010; Vizioli et al, 2000; Xia et al, 2013) and moricins (Brown et al, 2008; Dia et al, 2008; Hemmi et al, 2002). Proline-rich peptides with antifungal activity include lebocins (Chowdhury et al, 1995; Rao et al, 2012) and metchnikowin (Levashina et al, 1995; Rahnamaeian et al, 2009; Rahnamaeian and Vilcinskas, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is positively charged and can form specific amphipathic a-helices to interact with the non-polar lipid cell membranes [12,22]. CecropinXJ could kill cancer cells but have no hemolytic activity against human erythrocytes and no toxicity to some normal cells [23]. In this study, we investigated the effects of cecropinXJ on cytoskeleton in human esophageal carcinoma Eca109 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have shown that cecropinXJ can inhibit the proliferation of human gastric cancer in vitro such as AGS cells (21), but have no hemolytic activity against human erythrocytes and no toxicity to normal mammalian cells (22,23). Due to difficulty of AGS cells to form a solid tumor in vivo, we investigated the cytotoxicity and the mechanism of cecropinXJ against the human gastric cancer BGC823 cells in the present study.…”
Section: Introductionmentioning
confidence: 99%